The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1155/2022/3676444
|View full text |Cite|
|
Sign up to set email alerts
|

Growth Differentiation Factor 7 Prevents Sepsis-Induced Acute Lung Injury in Mice

Abstract: Objective. Acute lung injury (ALI) is a life-threatening complication during sepsis and contributes to multiple organ failure and high mortality for septic patients. The present study aims to investigate the role and molecular basis of growth differentiation factor 7 (GDF7) in sepsis-induced ALI. Methods. Mice were subcutaneously injected with recombinant mouse GDF7 Protein (rmGDF7) and then intratracheally injected with lipopolysaccharide (LPS) to generate sepsis-induced ALI. Primary peritoneal macrophages we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…GDF7 can reduce inflammation and oxidative stress by downregulating stimulator of interferon genes, promoting adenosine 5′monophosphate (AMP)-activated protein kinase (AMPK) phosphorylation, and improving LPS induced lung injury in septic mice; the 72 h survival rate of septic mice treated with GDF7 exceeds 50% [ 27 ].…”
Section: Proteins and Peptidesmentioning
confidence: 99%
“…GDF7 can reduce inflammation and oxidative stress by downregulating stimulator of interferon genes, promoting adenosine 5′monophosphate (AMP)-activated protein kinase (AMPK) phosphorylation, and improving LPS induced lung injury in septic mice; the 72 h survival rate of septic mice treated with GDF7 exceeds 50% [ 27 ].…”
Section: Proteins and Peptidesmentioning
confidence: 99%
“…Accordingly, Zhou et al demonstrated that GDF7 promotes human adipose-derived stem cell differentiation in vitro [ 14 ]. In addition, Dong et al found that GDF7 ameliorates sepsis-induced acute lung injury by regulating the STING/AMPK pathway [ 15 ]. Interestingly, GDF7 mRNA levels in blood cells are elevated in patients with liver cirrhosis compared to healthy controls [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%